Multiplexed Imaging of Protein Phosphorylation on Membranes Based on TiIV Functionalized Nanopolymers. (1st April 2016) - Iliuk, Anton; Li, Li; Melesse, Michael; Hall, Mark C.; Tao, W. Andy
Abstract: Accurate protein phosphorylation analysis reveals dynamic cellular signaling events not evident from protein expression levels. The most dominant biochemical assay, western blotting, suffers from the inadequate availability and poor quality of phospho‐specific antibodies for phosphorylated proteins. Furthermore, multiplexed assays based on antibodies are limited by steric interference between the antibodies. Here we introduce a multifunctionalized nanopolymer for the universal detection of phosphoproteins that, in combination with regular antibodies, allows multiplexed imaging and accurate determination of protein phosphorylation on membranes. Abstract : Playing nicely together : Nanosized pIMAGO‐Fluor binds to a target with a total protein antibody without steric hindrance. Multiplexed detection of phosphorylation and total protein levels can provide critical information about the true relative level of phosphorylation on membranes in western blotting or microarrays.